TAX AVOIDANCE SEKTOR REAL ESTATE DAN PROPERTI: MODERASI UKURAN PERUSAHAAN ATAS LEVERAGE, PROFITABILITAS, PERTUMBUHAN PENJUALAN: TAX AVOIDANCE IN REAL ESTATE AND PROPERTY: FIRM SIZE MODERATES LEVERAGE, PROFITABILITY, SALES GROWTH - Hikmah, Aifa Izzwatul; Zuraidah, Zuraidah (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study aims to examine the effects of sales growth, profitability, and leverage on tax avoidance strategies, with firm size tested as a moderating variable. Using a sample of 18 real estate and property companies listed on the Indonesia Stock Exchange from 2019 to 2023, the study employs multiple regression and moderated regression analysis (MRA). The results show that profitability has a significant positive effect on tax avoidance, while leverage and sales growth do not have significant effects. Furthermore, firm size does not moderate the relationship between leverage, profitability, or sales growth and tax avoidance. This study contributes to the existing literature by providing sector-specific evidence and by highlighting the limited role of firm size as a moderating factor. The findings offer practical insights for companies in managing their tax strategies more effectively to ensure both tax savings and compliance with applicable regulations.